Effect Between Quality of Nursing Service on Inpatient’s Loyalty and Satisfaction in dr. Soepraoen Hospital Malang - Suardini Yudhawati, Ni Luh Putu (Journal for Research in Public Health, 2019)
The dimensions of service quality are factors that can affect the competitiveness and success of hospitals. In addition, the increasing competition between hospitals has led to the fact that each hospital can pay more attention to increasing patient satisfaction through the provision of quality services. Nursing services also greatly affect the level of patient loyalty. The purpose in this study was to determine the effect of the quality of nursing services on inpatient’s loyalty and satisfaction in dr. Soepraoen Army Hospital Malang. Design of this study is quantitative with a cross sectional approach. The data analysis technique used is path analysis using the value α of 0.05. The sample in this study were 268 respondents. The results of the data analysis showed that the quality of nursing services had a significant effect on patient satisfaction as indicated by the p-value of 0.000 and the coefficient (beta) of 0.948. Satisfaction has a significant effect as indicated by the p-value of 0.000 and the coefficient (beta) of 0.691. Besides that service quality has a significant influence on patient loyalty as indicated by the p-value of 0.000 and the coefficient (beta) of 0.270, and based on indirect effects obtained by the coefficient (beta) 0.065. The conclusion of the study shows that the quality of nursing services has an influence on patient satisfaction, the quality of Nursing Services has an influence on patient loyalty, and the quality of nursing services has an influence on inpatient loyalty and satisfaction at the dr. Soepraoen Army Hospital Malang.